"Not Alone Anymore": The Experiences of Adults With Diabetes in New York's Medicaid Health Home Program. Issue 6 (June 2020) - Mayer, Victoria L.; Siscovick, David; Goytia, Crispin; Brown, Daphne; Hanlen, Emily; Flory, James; McKee, M. Diane; Horowitz, Carol R.
Abstract : Background: New York State Medicaid's Health Home program is an example of a natural experiment that could affect individuals with diabetes. While evaluations of interventions such as the Health Home program are generally based solely on clinical and administrative data and rarely examine patients' experience, patients may add to the understanding of the intervention's implementation and mechanisms of impact. Objective: The objective of this study was to qualitatively examine the health and nonmedical challenges faced by Medicaid-insured patients with diabetes and their experiences with the services provided by New York's Health Homes to address these challenges. Research Design: We performed 10 focus groups and 23 individual interviews using a guide developed in collaboration with a stakeholder board. We performed a thematic analysis to identify cross-cutting themes. Subjects: A total of 63 Medicaid-insured individuals with diabetes, 31 of whom were enrolled in New York's Health Home program. Results: While participants were not generally familiar with the term "Health Home, " they described and appreciated services consistent with Health Home enrollment delivered by care managers. Services addressed challenges in access to care, especially by facilitating and reminding participants about appointments, and nonmedical needs, such as transportation, housing, and help at home. Participants valued their personal relationships with care managers and the psychosocial support they provided. Conclusions: From the perspective of its enrollees, the Health Home program primarily addressed access to care, but also addressed material and psychosocial needs. These findings have implications for Health Home entities and for research assessing their impact. Abstract : Supplemental Digital Content is available in the text.